Description of Bagarius vegrandis, a new species of sisorid catfish from Indochina (Actinopterygii: Siluriformes), with notes on the identity of Bagarius bagarius - Ng, Heok Hee; Kottelat, Maurice (Zootaxa, 2021)
Bagarius vegrandis, new species, is described from the Chao Phraya and Mekong river drainages. It differs from congeners in having a small maximum body size (to 220 mm SL vs. 520–1400 mm SL) and the adipose-fin origin markedly posterior to (vs. at vertical through or very slightly posterior to) the anal-fin origin. It further differs from congeners in having the following unique combination of characters: ovoid unculiferous plaques on dorsal surface of head, lateral margin of frontal not significantly deflected dorsally, eye diameter 11–15% HL, interorbital distance 23–28% HL, head width 18.3–22.3% SL, head depth 11.1–14.1% SL, filamentous extensions to first pectoral-fin element reaching to anus, dorsal spine width 10.6–13.9 times in its length, body depth at anus 8.7–12.0% SL, neural spines of the 4–6 vertebrae immediately anterior to adipose fin distally flattened but not forming series of prominent bumps along dorsal midline, length of adipose-fin base 10.8–13.0% SL, caudal-peduncle length 19.0–22.4% SL, caudal-peduncle depth 3.2–4.2% SL, 19–20 preanal vertebrae, and 39–40 total vertebrae. Bagarius bagarius (Hamilton, 1822) is demonstrated to be a species restricted to the Indian subcontinent (with Bagrus yarrelli Sykes, 1839, Pimelodus platespogon Valenciennes, in Jacquemont, 1839 and Pimelodus carnaticus Jerdon, 1849 as junior subjective synonyms) and Bagarius lica Volz, 1903 resurrected from synonymy with B. yarrelli as a valid species from Southeast Asia.